Popular politics in the rural Western Cape, South Africa: a case study of Ruiterbos - Ghedi Alasow, Jonis (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
This thesis argues that the philosophical foundations upon which human beings have been engaged have, across various schools of thought, made the mistake of presuming that some people are more modern than others. This suggestion is refuted throughout this thesis. To do this, intellectual traditions that take the fundamental rationality of all human beings as an indispensable starting point are engaged to argue for the need to acknowledge that everyone in the 'now' is indeed, of the 'now'. This thesis connects these debates about modernity, rationality and humanity to the contemporary discussions around rural politics with particular reference to Ruiterbos in the Western Cape province of South Africa. By means of detailed empirical and ethnographic research, this thesis illustrates the issues around which people in Ruiterbos are politicised. Via this case study, the a priori assumption that rural politics will necessarily manifest itself only with respect to questions of land and agrarian reform or labour relations is complicated. The two issues around which people in Ruiterbos, during the time of this research, seem to be politicised "“ housing and education "“ are surfaced throughout this thesis. The thesis argues that the findings in this case study call for an expansion of the issues that are traditionally considered when the question of rural politics is raised. The often historicist approach that limits the possibilities for politics in rural areas should be suspended for an approach that takes popular politics and political agents in rural areas seriously. The thesis finally argues that the conclusions that are reached with respect to questions of modernity and rural politics ought to be adopted to allow for more detailed and thorough explanations of popular politics in places like Ruiterbos.
Keywords: Political participation -- South Africa -- Cape Town; South Africa -- Politics and government -- 1994-; Land tenure -- Political aspects -- South Africa; Land use, Rural -- Political aspects -- South Africa